LITERATUR REVIEW: PENGARUH MEDIA SOSIAL TERHADAP PENGGUNAAN BAHASA INDONESIA DAN KEMAMPUAN BERBAHASA SISWA SEKOLAH DASAR - Amilia Dwi Putri; Afifah Khairunnisa; M.Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of social media on the use of the Indonesian language among elementary school students. The research employed the Systematic Literature Review (SLR) method by reviewing scientific articles obtained from Google Scholar and Garuda databases. The article selection process was carried out through identification, screening, and selection stages based on the suitability of the title, abstract, and research content. From a total of 225 articles identified, 8 articles met the inclusion criteria and were relevant to the research topic. The results showed that social media, especially TikTok, WhatsApp, YouTube, and Instagram, has a significant influence on the language development of elementary school students. This influence can be seen in the increased use of slang, abbreviations, code-mixing, and informal language in daily communication. In addition to having negative impacts on the use of standard Indonesian, social media also provides positive impacts, such as improving speaking skills, communication creativity, and students’ confidence in expressing opinions. Social media can also be used as an interactive and engaging learning medium for elementary school students. Therefore, the role of teachers and parents is needed to supervise students’ use of social media so that they are able to use proper and correct Indonesian according to communication contexts.